Codon Usage Bias Correlates With Gene Length in Neurodegeneration Associated Genes - Khandia, Rekha; Saeed, Mohd.; Alharbi, Ahmed M.; Ashraf, Ghulam Md.; Greig, Nigel H.; Kamal, Mohammad Amjad (Frontiers in Neuroscience, 2022)
Codon usage analysis is a crucial part of molecular characterization and is used to determine the factors affecting the evolution of a gene. The length of a gene is an important parameter that affects characteristics of the gene, such as codon usage, compositional parameters, and sometimes, its functions. In the present study, we investigated the association of various parameters related to codon usage with the length of genes. In sixty genes related to neurodegenerative disorders, the G nucleotide was the most abundant and the T nucleotide was the least; however, T exhibited a significant association with the length of the gene at both the overall compositional level and the first and second codon positions. Codon usage bias (CUB) of these genes was affected by pyrimidine and keto skews. In gene segments with lengths below 1200 bp and above 2400 bp, CUB was positively associated with length. Analysis at the individual level using gene segments of various lengths showed that the CUB of eleven codons was affected by gene length. Codons TTA, GTT, GTC, TCA, GGT, and GGA exhibited a positive association with length, whereas codons GTA, AGC, CGT, CGA, and GGG showed a negative association. GC-ending codons were preferred over AT-ending codons. Overall analysis indicated that the association between CUB and length varies depending on the segment size; however, CUB of 1200–2000-bp gene segments is not affected by gene length.